Partisipasi Perempuan dalam Perhutanan Sosial: Studi Kasus di Lima Provinsi - Abby Gina Boang Manalu; Nur Iman Subono; Retno Daru Dewi G. S. Putri (Jurnal Perempuan, 2022)
Social Forestry (SF) is one of the government’s community-based forest management programs, which aims to balance environmental needs with the welfare of communities around the forest. However, in the program’s implementation, due to social norms and gender inequalities, women are often marginalized in access and management of SF. This study analyzes women’s participation in SF, primarily from the perspective and experience of women at the site level. This study used qualitative research; data mining was carried out through focus group discussions (FGD) and interviews with women at the site level and with assistance from civil society organizations (CSOs) in five provinces (Nanggroe Aceh Darussalam, Bengkulu, West Kalimantan, Central Sulawesi, and West Papua). This study shows how cultural barriers affect the forms and good practices of women’s participation in SF and their impacts.